1998
DOI: 10.1037/0096-1523.24.2.592
|View full text |Cite
|
Sign up to set email alerts
|

Processing of illegal consonant clusters: A case of perceptual assimilation?

Abstract: Evidence is presented for a perceptual shift affecting consonant clusters that are phonotactically illegal, albeit pronounceable, in French. They are perceived as phonetically close legal clusters. Specifically, word-initial /dl/ and /tl/ are heard as /gl/ and /kl/, respectively. In 2 phonemic gating experiments, participants generally judged short gates-which did not yet contain information about the 2nd consonant t\l-as being dental stops. However, as information for the /!/ became available in larger gates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
103
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 54 publications
9
103
0
1
Order By: Relevance
“…It is well known that ill-formed onsets tend to be misidentified (Dupoux, Kakehi, Hirose, Pallier, & Mehler, 1999;Dupoux, Pallier, Kakehi, & Mehler, 2001;Hallé, Segui, Frauenfelder, & Meunier, 1998;Massaro & Cohen, 1983). For example, English speakers misidentify the unattested onset tla as tela (Pitt, 1998).…”
Section: Sonority Restrictions As a Putative Output Universalmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that ill-formed onsets tend to be misidentified (Dupoux, Kakehi, Hirose, Pallier, & Mehler, 1999;Dupoux, Pallier, Kakehi, & Mehler, 2001;Hallé, Segui, Frauenfelder, & Meunier, 1998;Massaro & Cohen, 1983). For example, English speakers misidentify the unattested onset tla as tela (Pitt, 1998).…”
Section: Sonority Restrictions As a Putative Output Universalmentioning
confidence: 99%
“…A recent series of experiments, however, demonstrated that speakers favor onsets with large sonority clines to those with smaller clines even when both types of onsets are unattested in their language (Berent et al, 2007;Berent et al, 2008;Berent et al, 2009;Berent, 2008). Such preferences were inferred from the susceptibility of unattested onsets to undergo perceptual repair.It is well known that ill-formed onsets tend to be misidentified (Dupoux, Kakehi, Hirose, Pallier, & Mehler, 1999;Dupoux, Pallier, Kakehi, & Mehler, 2001;Hallé, Segui, Frauenfelder, & Meunier, 1998;Massaro & Cohen, 1983). For example, English speakers misidentify the unattested onset tla as tela (Pitt, 1998).…”
mentioning
confidence: 99%
“…Conversely, when the same phoneme was presented in a SLI (legal sequence) / SRI (illegal sequence) context, subjects identified the phoneme as an /l/. In a similar vein, Hallé, Segui, Frauenfelder, and Meunier (1998) presented nonce sequences beginning with either a legal (/tR/) or an illegal initial cluster (/tl/, /dl/) in French (e.g., trabdo or tlabdo, dlabdo, respectively). In two tasks (phonemic transcription and forced choice), they observed that coronal stops in illegal sequences (/t/, /d/ in tlabdo, dlabdo) were perceived as being velar stops (/k/ and /g/), although no velar information was present in the signal.…”
mentioning
confidence: 99%
“…This asymmetry between phonotactically legal and illegal forms is also found in the perception task, where forms with two ejectives are confusable with forms with a single ejective. These results suggest that the grammatical restriction is internalized by CQ speakers, and pervades production and perception, as found in much previous work (Werker and Tees 1984;Hallé et al 1998;Pitt 1998;Dupoux et al 1999;Hallé and Best 2007). The consistent effects of phonotactic legality across tasks is unsurprising given the categorical nature of the restriction against forms with multiple ejectives, as well as previous findings that pairs of ejectives are both generally articulatorily and perceptually challenging (Ohala 1981(Ohala , 1993; Gallagher 2010a, b; Gallagher and Whang to appear).…”
Section: Discussionmentioning
confidence: 53%
“…The null result on the perception study could be a result of the identity preference being only a production effect, or it could simply be that the preference for identity is not reflected in an ABX task. While some grammatical distinctions have been shown to influence perception (Werker and Tees 1984;Hallé et al 1998;Pitt 1998;Dupoux et al 1999;Moreton 2002;Hallé and Best 2007), other work has shown that perception is not equally influenced by all grammatical distinctions (Best et al 1988;Kabak and Idsardi 2007). A more varied range of tasks is needed to determine whether the identity preference is active only in production.…”
Section: Assessing the Role Of The Grammar And Productionmentioning
confidence: 99%